Liposomal Delivery of mRNA-Based Therapeutics for Personalized Cancer Immunotherapy: Design and Preclinical Insights - Ahuja, Dharmendra; Thakur, Shivangi; Debnath, Shubho; Basu, Anusree; Bhowmik, Mrinmoyee; Priya Singh, Kirti Goel; Khamkat, Piyali (Journal of Neonatal Surgery, 2025)
The use of messenger RNA (mRNA) medication in cancer has transformed cancer immunotherapy by letting researchers directly add tumor-related proteins and immune system boosters into the treatment. Still, naked mRNA has problems with instability and not being taken well by cells, so advanced methods of delivery are required. Researchers and manufacturers have made liposomal formulations the standard for mRNA, as these protect it from degradation, help it be taken up by cells and ensure controlled reactions. The goal of this review is to study the design concepts behind liposomal mRNA drugs for cancer immunotherapies and look at their formulation, how they operate and results from preclinical experiments. We examine significant measurements that impact how effective therapy is such as the makeup of lipids, particle size determination, targeting approaches and how much immune activation occurs. It has been shown in recent studies on animals that perfected liposomal mRNA vaccines can produce effective immunity against cancer by improving the transfection of dendritic cells, lasting antigen display and arousing both CD8+ and CD4+ T cell responses. Combining the detection of personalized neoantigens with liposomal delivery recently introduced a new cancer therapy which could minimize risk and be more effective overall for patients than the traditional treatments.